2021
DOI: 10.3855/jidc.14217
|View full text |Cite
|
Sign up to set email alerts
|

Avian pathogenic Escherichia coli (APEC) and uropathogenic Escherichia coli (UPEC): characterization and comparison

Abstract: Introduction: Avian pathogenic E. coli (APEC) and uropathogenic E. coli (UPEC) are responsible for avian colibacillosis and human urinary tract infections, respectively. There are genetic similarities between the APEC and UPEC pathotypes, suggesting the APEC strains could be a potential reservoir of virulence and antimicrobial-resistance genes for the UPEC strains. This study aimed to characterize and compare APEC and UPEC strains regarding the phylogroup classification, pathogenicity and antimicrobial suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…APEC can act as a primary or secondary pathogen in these cases [ 19 ]. APEC shares phylogenetic overlap with neonatal meningitis Escherichia coli (NMEC) and shares many virulence factors, such as type I fimbriae, invasins, and protectins [ 20 ]. Additionally, it has also been demonstrated that APEC can cause meningitis or bacteremia in mice, similar to NMEC [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…APEC can act as a primary or secondary pathogen in these cases [ 19 ]. APEC shares phylogenetic overlap with neonatal meningitis Escherichia coli (NMEC) and shares many virulence factors, such as type I fimbriae, invasins, and protectins [ 20 ]. Additionally, it has also been demonstrated that APEC can cause meningitis or bacteremia in mice, similar to NMEC [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Food animals are commonly regarded as important vectors for acquisition and transmission of ARGs from the environment to humans [19]. Studies have shown that antibiotic resistance genes (ARGs) have been detected not only in domestic animals, but also wildlife especially those that range close to human dwellings [20][21][22][23]. Ferreira et al [7] reported that AMR reduces therapeutic options and can increase the survival of the pathogen in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that the genomic features of APEC and human ExPEC are highly similar, with many genetic regions being homologous to each other. They also contain common virulence-related genes, cause similar disease patterns, and have similar evolutionary backgrounds ( 7 , 8 ). Therefore, we speculate that some APEC strains may pose a severe threat to public health ( 9 ).…”
Section: Introductionmentioning
confidence: 99%